A Microfluidic Approach for Investigating the Temperature Dependence of Biomolecular Activity with Single-Molecule Resolution - Wang, Bin (2010)
We present a microfluidic approach for single-molecule studies of the temperature-dependent behavior of biomolecules, using a platform that combines microfluidic sample handling, on-chip temperature control, and total internal reflection fluorescence (TIRF) microscopy of surface-immobilized biomolecules. With efficient, rapid, and uniform heating by microheaters and in situ temperature measurements within a microfluidic flowcell by micro temperature sensors, closed-loop, accurate temperature control is achieved. To demonstrate its utility, the temperature-controlled microfluidic flowcell is coupled to a prism-based TIRF microscope and is used to investigate the temperature-dependence of ribosome and transfer RNA (tRNA) structural dynamics that are required for the rapid and precise translocation of tRNAs through the ribosome during protein synthesis. Our studies reveal that the previously characterized, thermally activated transitions between two global conformational states of the pre-translocation (PRE) ribosomal complex persist at physiological temperature. In addition, the temperature-dependence of the rates of transition between these two global conformational states of the PRE complex reveal well-defined, measurable, and disproportionate effects, providing a robust experimental framework for investigating the thermodynamic activation parameters that underlie transitions across these barriers.